Four gathered on Christmas Eve - Powell, Eric; Mignola, Mike; Cloonan, Becky (Dark Horse Books, 2023)
"Four of the top creators in comics gather to continue the Victorian tradition of ghost stories on Christmas Eve. Four tales of the bizarre and terrifying to keep you company on the cold yule night. A unique approach to the ghost story format where the creators themselves become part of the story in this deluxe edition hard cover designed by the award-winning Phil Balsman"--